Improving Project Performance Based on Building Information Modelling 6D & LCCA in High-Rise Office Building - Prastowo, Ferdiansyah Ibnu; Husin, Albert Eddy; Amalia, Nur (ASTONJADRO, 2023)
Of the total 5.9 million existing buildings, the Office occupies the 2nd position of the most types of buildings with 16% of the Total Total. The least used aspect of BIM (Building Information Modeling) is the ability to obtain building energy models using the 6D BIM methodology. This digital information model is to simulate building energy and improve building energy systems. In this way, 6D BIM simulation allows us to make building design and operational decisions. In the case of increased energy, which leads to greater quality and comfort in the sustainable use of buildings. This issue has a special relationship in public buildings. Where energy efficiency and comfort are two fundamental criteria that are highly valued by society. Once the building's energy model is prepared, it will study and identify possible ones to improve energy efficiency, as well as analyze the incorporation of other, more efficient forms of renewable energy such as the use of natural light. From this research, "10 factors that affect cost performance in Office Building Projects" Maintenance costs, Use of Photovoltaic Solar Panel Materia, Model Obyetifiability, Office Equipment (TV, Computer, Printer etc.), Use of refrigen without ODP, Use of Elevators, Initial cost of retrofit, Materia Façade, Environmentally friendly materials.